Functional income distribution, capacity utilization, capital accumulation and productivity growth in Turkey: A post-Kaleckian analysis - Ozan Ekin Kurt (ZBW – Leibniz Information Centre for Economics, 2019)
The aim of this article is to examine the relation between functional income distribution, capacity utilization, capital accumulation and productivity in Turkey by identifying demand and overall regimes prevalent in the economy. For that purpose, we conduct an empirical analysis using different specifications of the post-Kaleckian model of Hein and Tarassow (2010). Depending on the specification employed, empirical findings point at two types of demand and overall regimes that might be prevailing in Turkey. In case of an intermediate demand regime along with a type of intermediate overall regime, pro-labor policies lead to an increase in the rates of capacity utilization and productivity growth, but a decline in the rate of accumulation. However, if a profit-led demand regime accompanied with an expansive overall regime rules, these policies are expected to lead to a fall in all these three variables. The findings show that, independent of specification, a higher profit share has a positive impact on the rate of accumulation; however, the effects on the rates of capacity utilization and productivity growth vary in sign and magnitude, though the latter are less than unity in absolute value. The article contributes to the literature by being the first study that simultaneously identifies demand and overall regimes of an economy.
Keywords: 330; Functional income distribution; growth; post-Keynesian economics; Turkey